The Impact of the RI-AS Trade Agreement on the Protection of Personal Data in Indonesia's Digital Trade - Ruqiah Ramadhany Efendi Pohan; Sherly Safitri; Nazriel Aidil Fahrezy; Farizza Ananta Baihaqi; Rifki Candra Firzatullah (ISNU Nine-Star Multidisciplinary Journal, 2026)
Cross-border digital trade has become an essential part of the modern global trading system. These developments prompted countries to establish trade agreements that not only govern the exchange of goods and services, but also include arrangements related to data and information. The trade agreement between the Republic of Indonesia and the United States is a form of cooperation that has direct implications for digital trade practices in Indonesia. This study aims to examine the impact of the Indonesia-US trade agreement on the protection of personal data in digital trade in Indonesia. The research method used is normative legal research with a statutory approach and a conceptual approach. The results of the study show that the Indonesia-US trade agreement has the potential to encourage the growth of digital trade, but at the same time poses challenges in ensuring personal data protection and legal certainty for consumers. Therefore, efforts are needed to harmonize international trade agreement commitments and national laws so that digital trade can flourish without overriding the protection of citizens' privacy rights.